Analisis Kemampuan Berpikir Komputasi Menggunakan Microsoft Math Solver (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study seeks to assess the involvement of an independent fishing insurance scheme that can be printed in Sibolga City. This type of research is known for its qualitative description. To obtain data, monitoring, conducting interviews and accessing paper The findings show that the Mandari Independent Fishermen's Insurance Program, which is supervised by the Director of Fisheries, complies with the direction of the Director General. It would be reasonable to have confidence in the independent fishing insurance program for fishermen. Fishermen's participation is influenced by a number of variables, especially internal factors that encourage internal participation. This program definitely requires fishermen's participation. Communication is a component that influences fishermen's participation in the independent fishermen insurance program, because communication is the process of exchanging information. The community often interacts and communicates to get additional information about the implementation of the independent fishermen insurance program. In addition, the community will become familiar and feel the benefits of the development program through intensive communication. They benefit from the program because good communication can encourage them to participate more. Next, the level of education, which is an important component that encourages community participation. One of the factors that influences a person's attitude towards the existing independent fishermen's insurance program is their age. In addition, because the work of fishermen is clearly a very risky job, social solidarity is the reason fishermen participate in the independent fishermen's insurance program. When fishermen go to sea, there are many things that can threaten their lives, such as direct contact with unpredictable sea waves, ocean storms, attacks by wild animals, and a number of other dangers. Judging from the level of success of the implementation of the fishermen's insurance premium assistance program that is right on target and in accordance with the provisions of the disbursement and the cause of the incident of the recipient of assistance, this policy indicator can show that the implementation of this policy has been carried out well. From the community support indicator, it can be concluded that the community is very supportive and fully participates in accepting this policy. Keywords: ,